2021
DOI: 10.1002/ange.202110585
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Integrated Copper‐Based Nanoparticles/Amorphous Metal–Organic Framework by a Facile Spray‐Drying Method: Highly Enhanced CO2 Hydrogenation Activity for Methanol Synthesis

Abstract: We report on Cu/amUiO‐66, a composite made of Cu nanoparticles (NPs) and amorphous [Zr6O4(OH)4(BDC)6] (amUiO‐66, BDC=1,4‐benzenedicarboxylate), and Cu‐ZnO/amUiO‐66 made of Cu‐ZnO nanocomposites and amUiO‐66. Both structures were obtained via a spray‐drying method and characterized using high‐resolution transmission electron microscopy, energy dispersive spectra, powder X‐ray diffraction and extended X‐ray absorption fine structure. The catalytic activity of Cu/amUiO‐66 for CO2 hydrogenation to methanol was 3‐f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…The performance of Cu/amUiO-66 for CO 2 hydrogenation to CH 3 OH was 3-fold higher compared to Cu/ crystalline UiO-66. [84] Furthermore, CuÀ ZnO/amUiO-66 reached STY for MeOH production of 710.5 μmol g Cu À 1 h À 1 , surpassing by a factor of 1.5-fold to the performance of Cu/ amUiO-66 and 2.5-fold to the productivity value for CuÀ ZnO/γ-Al 2 O 3 (Figure 10). In situ FT-IR spectroscopy and XPS measurements were performed to characterize the nature of support and understand its high activity.…”
Section: Methodsmentioning
confidence: 99%
“…The performance of Cu/amUiO-66 for CO 2 hydrogenation to CH 3 OH was 3-fold higher compared to Cu/ crystalline UiO-66. [84] Furthermore, CuÀ ZnO/amUiO-66 reached STY for MeOH production of 710.5 μmol g Cu À 1 h À 1 , surpassing by a factor of 1.5-fold to the performance of Cu/ amUiO-66 and 2.5-fold to the productivity value for CuÀ ZnO/γ-Al 2 O 3 (Figure 10). In situ FT-IR spectroscopy and XPS measurements were performed to characterize the nature of support and understand its high activity.…”
Section: Methodsmentioning
confidence: 99%
“…Chemie Minireviews ure 14b) utilized amorphous MOFs to protect Cu nanoparticles and Cu-ZnO nanocomposites, [193] and both of the synthesized catalysts Cu/amUiO-66 and Cu-ZnO/amUiO-66 exhibit a higher activity than that of Cu/crystalline UiO-66 and Cu-ZnO/γ-Al 2 O 3 for CO 2 hydrogenation to methanol. Lercher and co-workers (Figure 14c) anchored Cu ions on the Zr nodes of UiO-66 by ion-exchange method.…”
Section: Methodsmentioning
confidence: 99%
“…Mechanism studies revealed that the introduced Zn 2 + sites are responsible for H 2 activation, and Zn 2 + À OÀ Zr 4 + moieties are critical for CO 2 adsorption and conversion. Mitsuka and co-workers (Fig- ure 14b) utilized amorphous MOFs to protect Cu nanoparticles and Cu-ZnO nanocomposites, [193] and both of the synthesized catalysts Cu/amUiO-66 and Cu-ZnO/amUiO-66 exhibit a higher activity than that of Cu/crystalline UiO-66 and Cu-ZnO/γ-Al 2 O 3 for CO 2 hydrogenation to methanol. Lercher and co-workers (Figure 14c) anchored Cu ions on the Zr nodes of UiO-66 by ion-exchange method.…”
Section: Hydrogenation Of Comentioning
confidence: 99%